Polyphosphate kinase deletion increases laboratory productivity in cyanobacteria - Sebesta, Jacob; Cantrell, Michael; Schaedig, Eric; Hou, Harvey J. M.; Pastore, Colleen; Chou, Katherine J.; Xiong, Wei; Guarnieri, Michael T.; Yu, Jianping (Frontiers in Plant Science, 2024)
Identification and manipulation of cellular energy regulation mechanisms may be a strategy to increase productivity in photosynthetic organisms. This work tests the hypothesis that polyphosphate synthesis and degradation play a role in energy management by storing or dissipating energy in the form of ATP. A polyphosphate kinase (ppk) knock-out strain unable to synthesize polyphosphate was generated in the cyanobacterium Synechocystis sp. PCC 6803. This mutant strain demonstrated higher ATP levels and faster growth than the wildtype strain in high-carbon conditions and had a growth defect under multiple stress conditions. In a strain that combined ppk deletion with heterologous expression of ethylene-forming enzyme, higher ethylene productivity was observed than in the wildtype background. These results support the role of polyphosphate synthesis and degradation as an energy regulation mechanism and suggest that such mechanisms may be effective targets in biocontainment design.